Driving performance in exporter-importer exchange relationships: The efficacy of interorganizational trust as a response to exchange risks - A.F.M. Jalal Ahamed; Fabrizio Noboa (Cogent Business & Management, 2023)
Drawing on the transaction cost analysis perspective, this study examines how three types of exchange risks influence performance in exporter-importer exchange relationships. These risks include cultural distance, which gives rise to behavioral uncertainty and its associated measurement problem; market turbulence, a dimension of environmental uncertainty that gives rise to an adaptation problem; and transaction-specific assets, representing a safeguarding problem. The conceptual model assesses how an informal governance mechanism, inter-organizational trust, responds to these three exchange risks and, in doing so, fosters relational and export performance. Based on a structural equation model conducted in PLS, our findings indicate that cultural distance relates positively to inter-organizational trust, and market turbulence positively relates to exporter-specific assets. Exporter-specific assets and inter-organizational trust were found to have a reciprocal relationship. This research also confirms the mediating role of relational performance concerning the effects of exporter-specific assets and inter-organizational trust on financial export performance.
Keywords: 650; behavioral uncertainty; cultural distance; environmental uncertainty; Latin America; market turbulence